SIYASAH SYAR’IYYAH TENTANG PENGELOLAAN ZAKAT PADA MASA AWAL ISLAM - Arlis, Arlis (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2011)
One of the most appropriate parameters used to describe how zakat is supposed to be ideally managed is by tracing back to how it was done in the beginning era of Islam. This is the reasons why this research was done, that is, to figure out siyasah syar’iyyah of zakat management in the early periods of Islam and become the parameters for current situation expectedly. This study was a library research employing analytical descriptive approach. Based on the data obtained, it was understood that siyasah syar’iyyah in the early periods of Islam respected the principles of justice and prosperity and prioritized the commands of Allah compared to other considerations. In addition, In the era of Rasulullah SAW, the management of zakat was done by himself and assisted by the companions who were assigned to collect the zakat. Even in the era of Abu Bakar Siddiq, the policy on fulfilling the responsibility on zakat was made clear and strict. As a result, those Moslems who were reluctant to fulfill the responsibility would be regarded as the enemy of Islam. Though the implementation of the policy was made easier in the era of Ustman bin Affan, it did not indicate that (Islamic) state had less authority to manage zakat.